FATIGUE LIFE PREDICTION OF METAL MATERIALS BASED ON STRENGTH DEGRADATION - LIU SuChao; JIANG ChangJie; LIU XinTian (Jixie qiangdu)
In order to study the law of residual strength degradation of metal materials in the process of fatigue,a residual strength degradation model is established based on the definition of fatigue damage. The correctness of this model is verified by the previous experimental data. By comparing with the calculated data of other scholars ’ models,it is shown that the model proposed in this paper improves the calculation accuracy. At the same time,an improved equivalent damage model is proposed based on the residual strength degradation model,from which the fatigue cumulative damage model is derived. The cumulative damage model is applied to the estimation of fatigue residual life under two-stage load. And the influence of different loading sequence on fatigue life under variable amplitude load is explored. Combined with the experimental data,it is verified that the model can accurately estimate the fatigue life under two-stage load.